Project-Based Learning In Teachers Module - Asty, Herfyna (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the application of Project-Based Learning (PBL) in the English teaching module used by teachers. The approach used is qualitative with a document study method, with data obtained from the Independent Curriculum teaching module. The analysis was carried out using a checksheet based on project-based learning criteria. The results of the study show that the teaching modules used have met the PBL criteria according to the Independent Curriculum. This proves that as a driving school has implemented project-based learning effectively in the classroom. This module assists teachers in planning more structured and meaningful learning for students.